Youth employment in tourism: a multidimensional approach of job quality in Latin America - Dolcet, Malena (2024)
Young people entering the labor markets face several and important challenges. These issues deepen due to rooted structural barriers such as informality or precarity, low-paid jobs, and low economic growth in regions like Latin America and sectors such as tourism (Abramo, 2022). Tourism has great potential to employ many of these young people because it provides opportunities for skilled and unskilled workers, it has low barriers to entry and flexible conditions, and it provides critical skills for their professional life. However, the youth population needs to reduce the gap between their available skills and experienced gained and the future requirements of labor markets to avoid being socially excluded. We apply the multidimensional poverty methodology developed by Alkire and Foster (2011) to build a Quality of Employment index (QoE) for young workers employed in the tourism industry in Latin America for the period 2015-2019. Focusing on two groups of young workers -super young for those aged 15 to 24 and young those aged 25 to 35- we consider several aspects of working conditions and discuss some differences in job quality across countries by gender and education considering different levels of deprivation in the index. The results suggest a high level of deprivation in the young workers, specially in the super young group. However, employment quality increased in both groups for all countries in the region during the period 2015-2019.